TO THE DEFINITION OF THE CONCEPT 'GEOPEDAGOGICS' - I.V. BOGUSLAVSKIY; V.V. BOGUSLAVSKAYA (Advanced Engineering Research)
Substantiation and definition of the new concept ‘geopedagogics’ due to the global processes in the modern world are given in the article. The problem of education evolution and a new educational model formation is put.